Duration of Androgen Suppression in the Treatment of Prostate Cancer - (:unkn) unknown (MASSACHUSETTS MEDICAL SOC, 2009)
BACKGROUND The combination of radiotherapy plus long-term medical suppression of androgens (>= 2 years) improves overall survival in patients with locally advanced prostate cancer. We compared the use of radiotherapy plus short-term androgen suppression with the use of radiotherapy plus long-term androgen suppression in the treatment of locally advanced prostate cancer. METHODS We randomly assigned patients with locally advanced prostate cancer who had received external-beam radiotherapy plus 6 months of androgen suppression to two groups, one to receive no further treatment (short-term suppression) and the other to receive 2.5 years of further treatment with a luteinizing hormone-releasing hormone agonist (long-term suppression). An outcome of noninferiority of short-term androgen suppression as compared with long-term suppression required a hazard ratio of more than 1.35 for overall survival, with a one-sided alpha level of 0.05. An interim analysis showed futility, and the results are presented with an adjusted one-sided alpha level of 0.0429. RESULTS A total of 1113 men were registered, of whom 970 were randomly assigned, 483 to short-term suppression and 487 to long-term suppression. After a median follow-up of 6.4 years, 132 patients in the short-term group and 98 in the long-term group had died; the number of deaths due to prostate cancer was 47 in the short-term group and 29 in the long-term group. The 5-year overall mortality for short-term and long-term suppression was 19.0% and 15.2%, respectively; the observed hazard ratio was 1.42 (upper 95.71% confidence limit, 1.79; P=0.65 for noninferiority). Adverse events in both groups included fatigue, diminished sexual function, and hot flushes. CONCLUSIONS The combination of radiotherapy plus 6 months of androgen suppression provides inferior survival as compared with radiotherapy plus 3 years of androgen suppression in the treatment of locally advanced prostate cancer. (ClinicalTrials.gov number, NCT00003026.)
Keywords: QUALITY-OF-LIFE; PHASE-III; DEPRIVATION THERAPY; RADIATION-THERAPY; RADIOTHERAPY; ADJUVANT; TRIAL; IRRADIATION; MANAGEMENT; OUTCOMES